The Value of Inflammatory Biomarkers in Differentiating Asthma–COPD Overlap from COPD - Li M (International Journal of COPD, 2020)
Meng Li,* Tian Yang,* Ruiqing He, Anqi Li, Wenhui Dang, Xinyu Liu, Mingwei Chen Department of Respiratory and Critical Care Medicine of the First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi 710061, People’s Republic of China*These authors contributed equally to this workCorrespondence: Mingwei ChenDepartment of Respiratory and Critical Care Medicine of the First Affiliated Hospital of Xi’an Jiaotong University, 277 West Yanta Road, Xi’an, Shaanxi 710061, People’s Republic of ChinaTel/Fax +86-29-85323850Email chenmw36@163.comPurpose: To evaluate the accuracy of inflammatory biomarkers in differentiating patients with asthma–COPD overlap (ACO) from those with COPD alone.Methods: Clinical data of 134 patients with COPD and 48 patients with ACO admitted to the First Affiliated Hospital of Xi’an Jiaotong University from January 2016 to June 2019 were retrospectively analyzed. Receiver operating characteristic (ROC) curve analysis was performed to determine the best cut-off values of fractional exhaled nitric oxide (FeNO), blood eosinophil counts (EOS), and neutrophil to lymphocyte ratio (NLR) for differentiating between ACO and COPD alone. Spearman correlation analysis was conducted to evaluate the relationships between these inflammatory biomarkers and the forced expiratory volume in one second/prediction (FEV1%pred).Results: FeNO and EOS in the ACO patients were significantly higher than those in the COPD patients (FeNO: median 37.50 vs 24.50 ppb, P < 0.001; EOS: median 0.20 vs 0.10 × 109/L, P = 0.004). FeNO was positively correlated with FEV1%pred (r = 0.314, P = 0.030), while NLR was negatively correlated with FEV1%pred (r = − 0.372, P = 0.009) in patients with ACO. In addition, a positive correlation between FeNO and EOS was also found in ACO, especially in patients without history of inhaled corticosteroids (ICS) use (r = 0.682, P < 0.001). The optimal cut-off value of FeNO was 31.5 ppb (AUC = 0.758, 95% CI = 0.631– 0.886) in patients with smoking history, with 70.0% sensitivity and 89.9% specificity for differentiating ACO from COPD. In patients without history of ICS use, the best cut-off value of FeNO was 39.5 ppb (AUC = 0.740, 95% CI = 0.610– 0.870), with 58.3% sensitivity and 84.9% specificity. Among patients without history of ICS use and smoking, 27.5 ppb was optimal cut-off level for FeNO (AUC = 0.744, 95% CI = 0.579– 0.908) to diagnose ACO, with 81.8% sensitivity and 60.7% specificity, and the sensitivity was improved to 91.7% when FeNO was combined with EOS.Conclusion: The inflammatory biomarkers FeNO and EOS can be used as indicators for differentiating between ACO and COPD alone.Keywords: fractional exhaled nitric oxide, blood eosinophil counts, neutrophil to lymphocyte ratio, chronic obstructive pulmonary disease, asthma–COPD overlap